1986
DOI: 10.1007/bf01389504
|View full text |Cite
|
Sign up to set email alerts
|

Mullite corundum articles for electric furnace roofs

Abstract: The development of electrometallurgical processes, the construction and introduction into service of large tonnage arc electric furnaces, the hardening of service conditions for the refractories in these units, especially with the introduction of furnaces of superhigh capacity, require use to be made of high-grade refractory materials. Besides the increased resistance of the walls, one of the most urgent problems is to get an increase in the life of the roof linings in electric furnaces.Foreign practice and So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1987
1987
1987
1987

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In addi~ tion to high temperatures (up to 1800~ and higher) and thermal shocks, the roof refractories experience local thermal stresses and mechanical loads and are also subject to the action of melting dust having variations in chemical and mineral compositions [I, 2].Investigations conducted earlier showed that the use of mullite-corundum refractories in electric furnace roofs [3,4] is most effective with the use of them in combination with PKhS periclase-chromite parts (COST 10888-76) using specially developed methods of lining [5,6].This article presents the results of investigations of two lots of synthetic mullitecorundum refractories produced by direct synthesis with a single firing in the Experimental Plant of Eastern Refractory Institute [7] after service in the lO0-ton arc steel melting furnaces (DSP-I00) of Chelyabinsk Metallurgical Combine. In the first lot of parts the weight % of AI203 varied from 58 to 72%.…”
mentioning
confidence: 97%
“…In addi~ tion to high temperatures (up to 1800~ and higher) and thermal shocks, the roof refractories experience local thermal stresses and mechanical loads and are also subject to the action of melting dust having variations in chemical and mineral compositions [I, 2].Investigations conducted earlier showed that the use of mullite-corundum refractories in electric furnace roofs [3,4] is most effective with the use of them in combination with PKhS periclase-chromite parts (COST 10888-76) using specially developed methods of lining [5,6].This article presents the results of investigations of two lots of synthetic mullitecorundum refractories produced by direct synthesis with a single firing in the Experimental Plant of Eastern Refractory Institute [7] after service in the lO0-ton arc steel melting furnaces (DSP-I00) of Chelyabinsk Metallurgical Combine. In the first lot of parts the weight % of AI203 varied from 58 to 72%.…”
mentioning
confidence: 97%